2022
DOI: 10.1136/postgradmedj-2022-141638
|View full text |Cite
|
Sign up to set email alerts
|

Differential attainment in higher surgical training: scoping pan-specialty spectra

Abstract: IntroductionThis study aimed to evaluate differential attainment during higher surgical training (HST; all specialties) related to three ethnic cohorts: White UK (WUKG), Black and Minority Ethnic UK Graduates (BMEUKG), and International Medical Graduates (IMG).MethodAnonymised records of 266 HSTs (126 WUKG, 65 BMEUKG, 75 IMG; 7 years) in a single UK Statutory Education Body were examined. Primary effect measures were Annual Record of Competency Progression Outcome (ARCPO) and Fellowship of the Royal College of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Another study by Robinson et al [14] demonstrated similar pass rates between WUKGs and BME UKGs, but IMGs had signi cantly lower pass rates than all UKGs. The FRCS pass rates of WUKGs, BME UKGs and IMGs were 76.9%, 52.9%, and 53.9%, respectively, though these percentages were not statistically signi cantly different [15].…”
Section: Academic Achievementmentioning
confidence: 80%
See 4 more Smart Citations
“…Another study by Robinson et al [14] demonstrated similar pass rates between WUKGs and BME UKGs, but IMGs had signi cantly lower pass rates than all UKGs. The FRCS pass rates of WUKGs, BME UKGs and IMGs were 76.9%, 52.9%, and 53.9%, respectively, though these percentages were not statistically signi cantly different [15].…”
Section: Academic Achievementmentioning
confidence: 80%
“…This contrasts with other specialities in which men are the in-group and women are seen to underperform. Outside of O&G, in comparison to men, women are less likely to pass MRCS [3,13], receive satisfactory ARCP outcome [15,17], or receive positive feedback [24], whilst not performing the same number of procedures as men [29,30]. This often leads to poor self-con dence in women [27], which can then worsen performance [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations